Case Report: Paratesticular Rhabdomyosarcoma - Zhu, Yiyi; Zhu, Ziwei; Xiao, Yunyuan; Zhu, Zaisheng (Frontiers in Oncology, 2021)
Paratesticular rhabdomyosarcoma (RMS) accounts for only 7% of all the RMS cases. Due to the limited available data, there is no consensus on the diagnosis and management of the paratesticular tumors. Here, we interrogated two paratesticular RMS cases in 25 and 27-year-old men presenting with painless and rapidly growing mass in the scrotum. Whereas the data showed no upregulation of tumor markers such as β-human chorionic gonadotropin (β-HCG), alpha-fetoprotein (AFP), and lactate dehydrogenase (LDH), scrotal ultrasonography and magnetic resonance imaging indicated the existence of paratesticular and inguinal lesions respectively. There was local recurrence in one patient who underwent radical orchiectomy for the sarcoma one year ago. In addition, the CT scans showed no occurrence of distant metastasis. The two patients underwent radical inguinal orchiectomy or resection of the recurrent tumors with nerve-sparing retroperitoneal lymph node dissection. Histologic examination revealed embryonal RMS (eRMS) without lymph node metastasis. We highlight the importance of multi-disciplinary participation for paratesticular RMS detection and preoperative ultrasound-guided needle biopsy (UNB) for rapid confirmatory diagnosis. Complete surgical resection coupled with chemotherapy and radiotherapy is the main treatment option for the paratesticular RMS. In addition, sperm cryopreservation treatment and endocrine follow-up could increase the overall survival and quality of life of the patients.